THE EFFECTIVENESS OF INTERACTIVE GOOGLE EARTH-BASED MEDIA IN TEACHING HISTORY AT VOCATIONAL HIGH SCHOOLS: Efektivitas Media Interaktif Berbasis Google Earth Pada Pembelajaran Sejarah di SMK - petrisia, galih; Widodo, J. Priyanto; Wibowo, Satrio (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to develop an interactive learning media using Google Earth to enhance the effectiveness of history instruction at the vocational high school (SMK) level. The background of the study stems from the low levels of student interest and understanding regarding historical materials, which are often perceived as abstract and lacking contextual relevance. The research employed a Research and Development (R&D) approach, utilizing a modified version of the Borg and Gall development model. The participants in this study were eleventh-grade students enrolled in the Visual Communication Design (DKV) program at SMK PGRI 2 Sidoarjo. Data collection methods included observation, interviews, validation questionnaires completed by media and subject matter experts, and limited trails involving students. The results indicate that the Google Earth-based learning media developed in tsshis study has a high level of feasibility in terms of design, content, and interactivity. This media allows students to visually and spatially investigate historical event sites, in accordance with cognitive learning theory and constructivist theory, both of which highlight the importance of students’ active participation in knowledge construction. As a result, using interactive media that utilizes Google Earth has demonstrated an improvement in students’ understanding and involvement in history. Furthermore, the media supports the implementation of contextual and discovery learning, and is recommended for broader application in history learning at vocational schools.